2019
DOI: 10.1002/ijc.32105
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels and cancer incidence in 217,244 individuals from primary health care in Denmark

Abstract: Vitamin D has been linked to cancer development in both pre‐clinical and epidemiological studies. Our study examines the association between serum levels of vitamin D and cancer incidence in the Capital Region of Denmark. Individuals who had vitamin D analyzed at The Copenhagen General Practitioners Laboratory between April 2004 and January 2010 were linked to Danish registries with end of follow‐up date at Dec 31st 2014, excluding individuals with pre‐existing cancer. Cox regression models adjusted for age in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…a P-value for heterogeneity among the studies within each cancer type. www.nature.com/scientificreports/ skin cancer, with the hazard ratio seemed to peak around a vitamin D status of 80 nmol/L in the non-linear trend analysis 33 . Because of the limited number of studies included in our non-linear dose-response meta-analyses, mainly due to the missing information on the range of vitamin D levels, further studies should aim to clarify the shape of the dose-response relationship.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…a P-value for heterogeneity among the studies within each cancer type. www.nature.com/scientificreports/ skin cancer, with the hazard ratio seemed to peak around a vitamin D status of 80 nmol/L in the non-linear trend analysis 33 . Because of the limited number of studies included in our non-linear dose-response meta-analyses, mainly due to the missing information on the range of vitamin D levels, further studies should aim to clarify the shape of the dose-response relationship.…”
Section: Discussionmentioning
confidence: 92%
“…Thirteen cohort studies [24][25][26]28,29,[31][32][33][34]43,[51][52][53] were eligible for inclusion. Of these, ten studies were included in the metaanalysis of 25(OH)D level and skin cancer [24][25][26]28,29,[31][32][33]51,53 and four studies were included in the meta-analysis of vitamin D intakes from diet and supplement and skin cancer risk 32,34,43,52 (Table S1 and S2). Seven studies were from North America 24,26,28,29,32,34,43 , five from Europe 31,33,[51][52][53] , and one from Australia 25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] The most active metabolite form of vitamin D is 1,25-D3, which not only participates in maintaining calcium homeostasis, but also has some non-endocrine effects such as influencing cardiovascular disease, diabetes and cancers. [36,37] Previous studies have proved that high circulating levels of 1,25-D3 have the ability to prevent the development of cancer. [38] Expression and nuclear activation of the VDR are necessary for the function of vitamin D. Thus, genetic alternation of the VDR gene could lead to important defects in gene activation, which is bound to affect the biological effects of vitamin D. At present, a lot of studies have investigated the association between VDR polymorphism and LC susceptibility, but the specific correlation of them still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of four cohort studies reported a possible inverse association of ovarian cancer incidence and circulating 25(OH)D levels that did not reach statistical significance [18]. Mixed results were obtained in more recent ecologic studies [19,20], case-control [21], and cohort studies [22,23] as well. A Mendelian randomization study found that European women with genetically lowered 25(OH)D concentrations due to single nucleotide polymorphisms (SNPs) had higher susceptibility for ovarian cancer [3].…”
Section: Epidemiological Data On the Link Between Vitamin D And Ovarimentioning
confidence: 99%